An evaluation of factors which can affect the implementation of a health promotion programme under the Schools for Health in Europe framework. (August 2016) - Bennett, Annemarie E.; Cunningham, Cara; Johnston Molloy, Charlotte
Highlights: Primary school teachers acknowledge that school can positively affect child health. Teachers understand the essential elements of school health promotion. Health promotion programmes which add to teacher workload are negatively perceived. Teachers doubt their ability to promote health across the school community. Health promotion programmes must adapt to the organisational culture of a school. Abstract: The Health Promoting Schools concept helps schools to promote health in a sustainable and long-term fashion. However, developing the capacity to promote health in this way can be challenging when a busy teaching curriculum must be fulfilled. This study aimed to identify factors which affect the acceptability of health promotion programmes to the everyday school environment. Semi-structured qualitative interviews were audio-taped with primary school teachers in one Irish county and transcribed verbatim. The resulting transcripts were analysed using content analysis. Thirty-one teachers were interviewed. The factors which may adversely affect the acceptability of health promotion programmes include the: attitude of teachers towards an additional extra-curricular workload; lack of confidence amongst teachers to lead health promotion; and different organisational cultures between schools. When health promotion programmes under the Health Promoting Schools concept are being implemented, it's important to consider: the readiness for change amongst teachers; the resources available to increase staff capacity to promote health; and the ability of a programme to adapt to the different organisational cultures between schools.